The Meaning of Life in Tembang Macapat - Alyu RAJ, Aliffatullah; Prihartanti, Nanik (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2022)
Purpose: to understand and describe the meaning of human life in tembang macapat of Javanese. Methodology: This research used a qualitative approach, the method used in this research was phenomenological studies. The informants in this research were 2 informants. Informants were selected based on the criteria, thatweres someone who knows and understands everything about Tembang Macapat of Javanese. The data collection technique used in this research was interviews. Results : The results of the research describe that in the eleventh of the Tembang Macapat, there is a picture of the life cycle of human beings born to death. Tembang Macapat has several different versions caused by different points of view used by individuals in interpreting their lives. For individuals who explore, interpret, and implement the content of the tembang macapat, it will have a direct effect on emotions and how individuals take an attitude. Individuals tend to be better able to manage emotions and be able to calm themselves down when facing stressful siuations, so the attitude taken is also not a rash and emotion-driven attitude.